1987
DOI: 10.1016/0019-1035(87)90003-0
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of reflectance spectra of terrestrial, lunar, and meteoritic powders and frosts from 92 to 1800 nm

Abstract: The reflectance spectra of powdered samples of selected minerals, meteorites9 lunar materials and frosts are presented a s an aid in the interpretation of present and future remote sensing data of solar system ob jects. Spectra obtained in separate wavelength regions have been combined and normalized, yielding coverage from 92 to 1800 nm. Spectral features include relfectance maxima in the far UV region produced by valence-conduction interband transitions, and reflectance minima in the near UV, visible and nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 22 publications
7
133
1
Order By: Relevance
“…In the 1400−1800 Å wavelength region, a slight blue slope would be expected if water ice existed on the surface, due to a broad water ice absorption band centered around 1600 Å in the FUV. However, if water ice were detected with Alice, at the longer wavelengths beyond 1800 Å, outside of the absorption band, we should see a rise in the bidirectional reflectance of 67P (Hapke et al 1981;Wagner et al 1987;Hendrix & Hansen 2008), which we do not. In fact, the spectra presented here do not show indications of any absorption features or absorption edges.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the 1400−1800 Å wavelength region, a slight blue slope would be expected if water ice existed on the surface, due to a broad water ice absorption band centered around 1600 Å in the FUV. However, if water ice were detected with Alice, at the longer wavelengths beyond 1800 Å, outside of the absorption band, we should see a rise in the bidirectional reflectance of 67P (Hapke et al 1981;Wagner et al 1987;Hendrix & Hansen 2008), which we do not. In fact, the spectra presented here do not show indications of any absorption features or absorption edges.…”
Section: Discussioncontrasting
confidence: 57%
“…This is considered to be blue sloped because of the decrease with increasing wavelength and is consistent with the derived values of the single scattering albedo, w, which also decreases from 1425−1525 Å to 1700−1800 Å (Table 3). While a blue slope may be suggestive of water ice on the surface in this finite FUV region as seen in the laboratory (Hapke et al 1981;Wagner et al 1987), using Hapke modeling as in Hendrix & Hansen (2008) it has also been shown that the water ice spectrum is expected to have a red slope at these wavelengths due to the location of the edge of the FUV cut-off if water ice were present. Therefore, the FUV blue slope alone is inconclusive with respect to the presence of water ice.…”
Section: Photometric Correctionmentioning
confidence: 81%
“…The relative values of the ratios show that Pele is the darkest and Ra the brightest of the three targets in this wavelength region, which is similar to the reflectivities of these three regions in somewhat longer-wavelength UV imaging observations (Sartoretti et al 1996). λ 2400Å by Hapke et al (1981) and Wagner et al (1987) are in reasonable agreement, they disagree in absolute value with the more detailed laboratory measurements by Nash et al (1980) by approximately a factor of 5 (depending on the frost grain size assumed) at 2400Å. The Hapke-Wagner results are therefore generally scaled down to match the Nash et al value.…”
Section: Surface Reflectancementioning
confidence: 55%
“…(3) The overall shape of the Ra/Pele ratio spectrum ( Fig. 5b) matches well the reflectivity of SO 2 frost, which we have overplotted on the ratio using the measured frost reflectance of Wagner et al (1987).…”
Section: Modeling and Analysismentioning
confidence: 64%
“…Perhaps some mixture of samples could be found to approximate Lutetia's spectrum, but such an effort is beyond the scope of this paper. We note, however, that many of the materials measured by Wagner et al (1987) have spectral features shortward of 2000 Å, which are potentially observable by the Alice instrument during the Rosetta flyby.…”
Section: Discussionmentioning
confidence: 82%